Delegation Styles And Leadership Perceptions: A Comparison Of Malaysian And American Managers. - Sim, Daphne L.; Ansari, Mahfooz A.; Jantan, Muhamad (2004)
Can managers be perceived as good leaders through a culture of empowerment in multinational settings? This question was answered by employing a 3 (delegation styles:advisory; informational; extreme) x 2 (manager gender: male; female) x 2 (country:Malaysia; USA) factorial design--with the first factor as within-subjects and the last two as between-subjects.